Pengembangan Media Modul Pada Materi Penggunaan Array Mata Pelajaran Pemrograman Dasar Kelas XI Multimedia Di SMA Negeri 2 Gunung Talang Solok - Prawiro, Radius; Ariandi, Vicky; Afira, Riandana (LPPM Universitas Dharma Andalas, 2024)
Based on the results of a preliminary study, namely the results of interviews and observations with Basic Programming subject teachers. The researcher found that in the main material of Using Arrays in the Basic Programming subject, the teacher was the only main and only source in the class, especially in the basic programming subject. This makes it difficult for students to receive the material without guidance from the teacher. If in this process the teacher continues to use the same method, it will have an impact on the development of students in the class which includes the level of student understanding and the student development process regarding the material being taught. The purpose of developing module media is to create an effort to solve learning problems through needs analysis, so that through this media it is hoped that it can increase the achievement of learning objectives and improve student learning outcomes. This media development uses the ADDIE development model. The trial implementation was carried out in several stages, namely validation of material experts, media experts, and trials on students. The data collection method used structured interviews, questionnaires, and tests. The data analysis technique used the P formula which was used to measure percentages, then for the test instrument using the formula Rpbis and T-test in Class XI Multimedia at SMA Negeri 2 Gunung Talang Solok